Interaksi Sosial Antar Siswa Muslim Dengan Non Muslim Di Kelas XI IPS (Studi Di SMA Negeri 1 Nanga Taman Kabupaten Sekadau) - Deden Deden (Universitas Tanjungpura, 2020)
The purpose of this research is to know the cooperation, accommodation, and competition among Muslim non-Muslim students of class XI IPS SMAN 1 Nanga Taman. The research methodology that is used is observation technique, interview, and documentation study while, the tools of data collecting are observation, interview, and documentation. The results showed social interaction between the Muslim and non- Muslim students through spontaneous cooperation, undertaken without orders from anyone, direct cooperation, which is done at the behest of students by teachers, students do not differentiate between Muslims and non-Muslims. Accommodation in the form of tolerance, mutual respect, and respect, compromise when students discuss the group to get the maximum results, while the individual competition is the competition in gaining success in learning, competing to earn achievements, then the competition groups that compete for presenting the best presentation in the discussions, case this relates to learning activities in class and outside of class.